Meriones hurrianae Jerdon 1867 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Meriones hurrianae Jerdon, 1867. Mamm. India, p. 186. TYPE LOCALITY: India, Hurriana Dist. (= Hariana). DISTRIBUTION: Extreme S. E. Iran, Pakistan, and N.W. India (principally in the Thar Desert); perhaps Afghanistan. COMMENT: Occurrence in Afghanistan is dubious (DML). ISIS NUMBER: 5301410008092004001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 3), pp. 392-476 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 424, DOI: 10.5281/zenodo.7353031